Pautas de publicación y citación de los científicos de disciplinas con carácter marcadamente territorial. El caso de la Geología en España. - Martín Sempere, Mª José (Revista General de Información y Documentación, 2000)
Publishing and citation patterns of Spanish geologists are analysed. The study is based on the articles published in Spanish geology journals during the period 1995-1996, as well as on the opinion of Spanish researchers in the field, obtained through a specially created survey. The aim of this work is to deter mine the type of documents most frequently published and used by these scien tists. The study also tries to identify some of the characteristics oftheirresearch activity. Spanish geologists publish more frequently in domestic than in foreign 167 M. José Martin-Senspere ¡Jesús Rey Rocha Pautas de publicación y citación de los ciennficas.. journals, although the latter receive a higher number of citations. The study points out the irnportance to geologists of conference publications, mono graphs, reports, and maps, as publication and reference documents.